The Importance of Vocabulary Building in Language Learning - qizi, Abduolimova Maftuna Nurulloxon; qizi, Abdumutalova Mohlaroy Zaynobiddin (Journal of Innovation in Education and Social Research, 2024)
This article explores the importance of vocabulary building in language learning and provides effective strategies for learning and retaining new words.